Syntactic Touch: A Probe - Cárdenas-García, Jaime F. (New Explorations, 2024)
Since the mid-twentieth century, we live in the Information Age. An epoch prioritizing the primacy of information, on a par with matter and/or energy. This probe questions the primacy of information, explores the origin of syntactic information and discovers the ubiquity of our syntactic touch.